The Potential of Algae Spyrogyra peipingensis to Produce Nanogold in Batch Culture Medium - Arbaina Syahdinnur; Agusrahman Ekaputra Abas; Chitriani Armidha (International Journal of Applied Biology, 2018)
The biosynthesis of gold nanoparticles by using algae Spirogyra peipingensis was conducted. This research aimed to determine biosynthesis of gold nanoparticles by using algae Spirogyra peipingensis with different concentration and incubation time. The synthesis of gold nanoparticles using HauCl4 solution with variations of concentration 5 ppm, 10 ppm, 15 ppm and 20 ppm respectively in 1 liter of aquabidest. Algae Spirogyra peipingensis was grown in HauCl4 medium with the addition of 0.2 gr Sulfahri-01 nutrient. Then each 5 gram Spirogyra algae incubated in HAuCl4 medium with the addition of Sulfahri-01 0.2 gram nutrients. 4 hours long incubation under exposure to sunlight. Nanoparticle size determination is done by looking at the color that appears in the solution. From the results of the research, it is known that Spirogyra peipingensis algae is able to synthesize gold nanoparticles characterized by the color change in algae biomass from green to purple color after being treated and forming gold nanoparticles with size 40-60 NM. The best-used HAuCl4 consent is 5 ppm with the smallest particle size. KeywordIntracelullar, Spirogyra peipingensis,HAuCl4,Biosynthesis.  Article HistoryReceived 8 May 2017 Accepted 3 July 2017